Indentation Testing of Biological Materials - Argatov, Ivan; Mishuris, Gennady (Advanced Structured Materials, 2018)
This book presents a comprehensive and unifying approach to analytical identification of material properties of biological materials. Focusing on depth-sensing indentation testing, pipette aspiration testing, and torsion of soft tissues, it discusses the following important aspects in detail: damping, adhesion, thickness effect, substrate effect, elastic inhomogeneity effect, and biphasic effect. This book is intended for advanced undergraduate and graduate students, researchers in the area of biomechanics as well as for biomedical engineers interested in contact problems and involved in inverse materials parameters prediction analysis.